Partial Humeral Head Arthroplasty, Glenoid Allograft Augmentation, and Open Bankart Reconstruction for Critical Glenoid Bone Loss and Engaging Hill-Sachs Lesion - Bradley L. Young MD; Spero G. Karas MD (SAGE Publishing, 2023)
Background: Shoulder instability with critical bipolar bone loss can be difficult to treat. Anterior glenoid bone block augmentation and partial humeral head resurfacing is a viable option. Indications: This procedure is indicated in patients with both critical anterior glenoid bone loss (≥20%) and an engaging Hill-Sachs lesion. Technique Description: A deltopectoral approach is performed, followed by a subscapularis tenotomy. The Hill-Sachs lesion is resurfaced with a partial humeral head arthroplasty. The anterior glenoid bone loss is replaced with a prefabricated allograft. An open Bankart repair is then performed. Results: Three case reports give evidence that this technique is a viable surgical option for patients with critical glenoid bone loss and an engaging Hill-Sachs lesion. Discussion/Conclusion: Partial humeral head resurfacing, glenoid allograft augmentation, and open Bankart is a viable surgical option for patients with critical anterior glenoid bone loss and an engaging Hill-Sachs lesion. Patient Consent Disclosure Statement: The author(s) attests that consent has been obtained from any patient(s) appearing in this publication. If the individual may be identifiable, the author(s) has included a statement of release or other written form of approval from the patient(s) with this submission for publication.